2015
DOI: 10.1039/c5cy00117j
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the role of a structural promoter (Ba) in three-way catalyst Pd/CeO2–ZrO2 using in situ DRIFTS

Abstract: A series of Pd/CeO 2 -ZrO 2 (Pd/CZ) catalysts modified with barium oxide with different contents were prepared and characterized by XRD, BET, XPS, H 2 -TPR and NO x adsorption/desorption-MS. In particular, the effect of a structural promoter (Ba) on the catalytic and surface behaviour was investigated by means of in situ DRIFTS. Doped Ba enters into the CeO 2 lattice, and thus results in the formation of more homogenous Ce-Zr-Ba ternary solid solution, which enhances the textural/structural thermostability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Yang et al 42 and Lan et al 43 looked into the addition of BaO to Pd/CeO 2 -ZrO 2 and Pd/CeO 2 -ZrO 2 -Al 2 O 3 , respectively. Yang et al found that it was possible to synthesize a homogeneous single-phase Ce/Zr/Ba solid solution with enhanced reducibility.…”
Section: Washcoat Compositionmentioning
confidence: 99%
“…Yang et al 42 and Lan et al 43 looked into the addition of BaO to Pd/CeO 2 -ZrO 2 and Pd/CeO 2 -ZrO 2 -Al 2 O 3 , respectively. Yang et al found that it was possible to synthesize a homogeneous single-phase Ce/Zr/Ba solid solution with enhanced reducibility.…”
Section: Washcoat Compositionmentioning
confidence: 99%
“…After thermal aging treatment, Zr-rich catalysts (CeO2/ZrO2 < 1) underwent less severe deterioration of the catalytic activity compared with Ce-rich catalysts (CeO2/ZrO2 ≥ 1) due to better thermal stability, and Pd/Ce0.5Zr0.5O2BaO presented the optimally catalytic performance. Subsequently, they probed the role of Ba in TWCs Pd/Ce0.5Zr0.5O2 using in-situ DRIFTS [481]. The introduction of Ba weakened the strong adsorption of HC reactants on the catalyst surface and accelerated NO dissociation.…”
Section: Effect Of Alkali or Alkali-earth Metals Dopingmentioning
confidence: 99%
“…The XPS spectra of the fresh and redox aged Pd/CZO samples are shown in Figure 3. The Pd 3d peaks were fit under the raw data between the shoulders of the Zr 3p peaks as is typically performed for analysis of Pd on CZO support [48,49,50,51]. The fresh Pd/CZO sample had two Pd 3d 5/2 peaks, at 334.7 eV for Pd metal and at 337.1 eV for Pd +2 .…”
Section: Xps Surface Characterizationmentioning
confidence: 99%